Influence of Composition of Waterborne Epoxy-Modified Cement-Based Coating Materials on Their Mechanical Properties - LIU Hao; LI Haifeng; REN Mengmeng (Renmin Zhujiang)
Coating protection is widely recognized as the primary barrier against erosion by aggressive agents. Polymer-modified cement-based coating materials not only retain the high adhesion and excellent water resistance of polymers but also possess the high strength and high weather resistance of cement-based materials. They have now become the most promising environmentally friendly composite coating material system in the field of water conveyance tunnel protection. Waterborne epoxy resin is one of the commonly used modified polymers due to its good compatibility with cement-based materials. In this study, to investigate the influence of the composition of waterborne epoxy resin-modified cement-based coating materials (WMC) on their mechanical properties, a series of WMC specimens were prepared by regulating two mix ratio parameters, which were the mass ratio of waterborne epoxy resin to curing agent and the mass ratio of emulsion to powder. The mechanical properties of WMC specimens at different curing ages were tested. The multi-scale characterization of specimens with significant performance differences was conducted by comprehensively applying low-field nuclear magnetic resonance, Fourier transform infrared spectroscopy, backscattered electron scanning electron microscopy, and nanoindentation techniques. At the same time, the main influencing mechanism of the material composition of WMC on performance was analyzed. The results show that the mechanical properties of WMC at different curing ages first increase and then decrease with the increase in waterborne epoxy resin dosage, and the mechanical properties gradually increase with the increase in powder dosage. Low-field nuclear magnetic resonance results show that excessive waterborne epoxy resin exerts an inhibitory effect on the early hydration of cement, which delays the densification of the microstructure of slurry and leads to a lower early strength of the specimen. After 28 days of curing, the waterborne epoxy resin in WMC has been completely cured, forming a relatively complete polymer film. Furthermore, in samples with excessive waterborne epoxy resin, the polymer emulsion can form a film structure to coat the surface of the hydration products. In addition, when the dosage of the polymer emulsion is too high, due to the self-drying effect within the cement paste, the excess waterborne epoxy resin can form micron-sized aggregates in the hardened paste. Moreover, the nanoindentation results show that the content of ultra-low density C-S-H in the hydration products will also increase, while the content of high-density C-S-H will decrease. The overall stiffness of the sample will decline, and it will be more prone to failure when subjected to the same level of load, ultimately leading to a decline in mechanical properties. Therefore, precisely controlling the dosage of waterborne epoxy resin is the key to achieving high performance of waterborne epoxy resin-modified cement-based materials.